2019
DOI: 10.1371/journal.pone.0212277
|View full text |Cite
|
Sign up to set email alerts
|

Valuing individual characteristics and the multifunctionality of urban green spaces: The integration of sociotope mapping and hedonic pricing

Abstract: We categorize Stockholm’s urban green spaces according to the use values and social meanings they support, based on a sociotope mapping, and estimate their impact on property prices with a hedonic pricing model. The approach allows us to identify the most and least desired green space characteristics (attributes) and to assess the willingness to pay for the multifunctionality of green spaces. To do this, we test the following hypotheses, each with a separate hedonic pricing model: the proximity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 46 publications
2
16
1
Order By: Relevance
“…In some cases, the size of a facility was found to be negatively correlated with WTP [11]. This clearly indicates the cost-benefit relationship of urban green spaces; the size of green facilities might be related to health and wellness benefits but may come with costs in the form of increased animals fouling, disturbance [43], or increased traffic or usage [14].…”
Section: Nature Within Reachmentioning
confidence: 91%
See 3 more Smart Citations
“…In some cases, the size of a facility was found to be negatively correlated with WTP [11]. This clearly indicates the cost-benefit relationship of urban green spaces; the size of green facilities might be related to health and wellness benefits but may come with costs in the form of increased animals fouling, disturbance [43], or increased traffic or usage [14].…”
Section: Nature Within Reachmentioning
confidence: 91%
“…The size of, and distance from, GI amenities have significant effects on individual appraisal, utility, and weighting in cost-benefit analysis. A number of studies found that people were willing to pay a premium to increase the coverage of green areas [8,44,47,60,61] and to decrease the distance between household and green urban spaces [8,[11][12][13]43,44,60]. Additionally, a significant relationship was Atmosphere 2020, 11, 152 8 of 20 found between mental health and distance to GI; increasing distance to green urban areas was found to significantly decrease life satisfaction [60,62].…”
Section: Nature Within Reachmentioning
confidence: 99%
See 2 more Smart Citations
“…Opportunities to realize different ideas and needs are not equally open to everyone (Biernacka and Kronenberg 2018, Czembrowski et al 2019). A first sharp divider is the difference between private and public, and ownership history is a key determinant of present-day property rights, as well as the expectations of responsibility and access.…”
Section: The Institutional Setting: Land-use Rights and Collectively mentioning
confidence: 99%